Sosialisasi Pentingnya Etika Bisnis Dalam Aktivitas Produksi UMKM Rengginang Di Kelurahan Rontu Kota Bima - kartin Aprianti; Umul Hidayati; Muh. Bahtiar (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
The purpose of this activity is that MSME actors can understand the importance of applying ethical principles in doing business, MSME actors are willing to participate in the socialization of understanding the application of ethical principles in business and understand the application of ethical principles in business. The implementation method used is by means of lectures and discussions using leaflets. The material provided includes discussion of (1) the role of ethics in doing business for MSME actors, (2) the benefits of doing business for MSME actors and (3) the application of ethical principles in doing business for MSME actors.